2021
DOI: 10.1111/1467-9566.13244
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional analysis of cannabis use, stigma and health among marginalized Nigerian women

Abstract: Cannabis use by women has been under‐researched, particularly use by marginalized women in developing societies. This article draws on qualitative research in Uyo, Nigeria, to explore how intersecting stigmas around social identity categories (e.g. gender, sex work) shapes cannabis use and contributes to health harms for marginalized women. Qualitative data were collected via in‐depth interviews with street‐involved female cannabis users, and transcribed, coded and analysed thematically. Initiation of cannabis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 64 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…The participants were men between 26 and 45 years (mean = 35.5 years). Female drug dealers could not be reached due to severe stigma and fear (Nelson, 2021). Fourteen of the 31 participants were unemployed, 6 were students and 11 were engaged in other economic activities (e.g.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…The participants were men between 26 and 45 years (mean = 35.5 years). Female drug dealers could not be reached due to severe stigma and fear (Nelson, 2021). Fourteen of the 31 participants were unemployed, 6 were students and 11 were engaged in other economic activities (e.g.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…Many make a living from street sex work, which has brought them into the proximity of drug dealing and use (Izugbara, 2007; Nelson, 2020). Women’s substance use has been shown to be woven into multiple and overlapping dynamics of social and economic marginalization, including poverty, homelessness, and criminalization and stigmatization of sex work and drug use, which shape substance use practices (Nelson, 2020, 2021; Nelson & Bridget, 2022).…”
Section: Study Context and Aimsmentioning
confidence: 99%
“…Recent studies have contributed to a better understanding of women’s substance use by explicating how structural and environmental factors shape substance use patterns and harms (Bourgois et al, 2004; Bungay et al, 2010; Collins et al, 2018; Epele, 2002; Fairbairn et al, 2008; McNeil et al, 2014; Saleem et al, 2021; Shannon et al, 2008). Studies have shown how initiation of substance use among women is influenced by social networks, which also mediate drug supply (Martin, 2010; Mburu et al, 2019; Meyers et al, 2020; Nelson, 2021). Women consume drugs in response to complex personal needs or problems such as the desire for intimacy, health improvement or for pleasure (Martin, 2010; Nelson, 2021; Payne, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 40.1% of Nigerians (about 82.9 million people) live in poverty (World Bank, 2022). Nelson and Tasha (2021) have shown how retail drug trade serves as a means of income generation for many Nigerian youth in the context of poverty and deprivation.…”
Section: Introductionmentioning
confidence: 99%